The depository fund of international organizations and its use in scientific library of Vilnius university - Balsytė, Raimunda (Knygotyra, 1983)
Nowadays the role of international organizations has risen. The international organizations developing their activities solve actual political, economical and cultural problems. The solutions of these problems appear in their publications and documents which are used by separate countries solving their local questions. In order to make their publications and documents freely available throughout the world, the international organizations have created a system of depository libraries. These libraries get the material issued by international organizations. Each country seeks to have such a centre of documents, to become a member of United Nations depository libraries system or other international organizations. The scientific library of Vilnius university fulfils this function in our republic. The article reveals the creation of UN depository libraries system, its present state, the function of Dag Hammarskjold library at the UN Headquarters. The main attention is paid to the depository fund of United Nations (UN), United Nations Educational, Scientific and Cultural Organization (UNESCO) and World Health Organization (WHO) in scientific library of Vilnius university. The history of its creation, its structure, maintenance of the collection, use of fund are being described in the article. The efforts to advocate documents of international organizations in public is also mentioned here.